Properties of High Strength Concrete Containing Class F Fly Ash - Nath, Pradip; Sarker, Prabir (Nova Science Publications Inc., 2014)
Fly ash, being a by-product, is a readily available material for potential utilization in various Civil Engineering applications. Utilization of fly ash as a supplementary cementitious material adds sustainability to concrete by reducing the greenhouse gas emission associated with cement production. However, different fly ash affects the properties of concrete differently because of the variation of its source, burning process and resulting chemical composition. This chapter discusses the properties of fly ashes produced in Australia and investigates the mechanical and durability properties of high strength concrete using a Class F fly ash. Fly ash concretes using 30% and 40% fly ash as cement replacement were designed with and without adjusting water to binder ratio (w/b) and total binder content. Concrete samples having high compressive strength varying in the range of 65 to 85 MPa were tested for shrinkage, water permeability and corrosion resistance properties. Concretes, in which mix proportions were adjusted for fly ash inclusion achieved equivalent control concrete strength and showed less drying shrinkage, sorptivity, water permeability, and chloride penetration than those in which adjustments were not made. Fly ash concretes showed similar carbonation as compared to the control concrete of similar grade. The durability properties improved with the increase of fly ash content from 30% to 40% of the binder and with the increase of age. The results show the suitability of using class F fly ash as substantial parts of the binder for making high strength concrete of good durability.